Self-assembling peptides cross-linked with genipin: resilient hydrogels and self-standing electrospun scaffolds for tissue engineering applications. (26th November 2018) - Pugliese, Raffaele; Maleki, Mahboubeh; Zuckermann, Ronald N.; Gelain, Fabrizio
Abstract : Molecular cross-linking with genipin enables the production of resilient standard and electro-spun self-standing scaffolds made of self-assembling peptides. Abstract : Self-assembling peptides (SAPs) are synthetic bioinspired biomaterials that can be feasibly multi-functionalized for applications in surgery, drug delivery, optics and tissue engineering (TE). Despite their promising biocompatibility and biomimetic properties, they have never been considered real competitors of polymers and/or cross-linked extracellular matrix (ECM) natural proteins. Indeed, synthetic SAP-made hydrogels usually feature modest mechanical properties, limiting their potential applications, due to the transient non-covalent interactions involved in the self-assembling phenomenon. Cross-linked SAP-hydrogels have been recently introduced to bridge this gap, but several questions remain open. New strategies leading to stiffer gels of SAPs may allow for a full exploitation of the SAP technology in TE and beyond. We have developed and characterized a genipin cross-linking strategy significantly increasing the stiffness and resiliency of FAQ(LDLK)3, a functionalized SAP already used for nervous cell cultures. We characterized different protocols of cross-linking, analyzing their dose and time-dependent efficiency, influencing stiffness, bioabsorption time and molecular arrangements. We choose the best developed protocol to electrospin into nanofibers, for the first time, self-standing, water-stable and flexible fibrous mats and micro-channels entirely made of SAPs. This work may open the door to the development and tailoring of bioprostheses entirely made of SAPs for different TE applications.